Efficiency enhancement of solution processable organic light emitting diodes via charge injection and transport modification / Noor Azrina Talik Sisin - Noor Azrina , Talik Sisin (2016)
iv ABSTRACT This research work aims at improving the device efficiency of solution processed OLED and at the same time to do in-depth study on the device charge injection and transport. The first research project demonstrates high efficiency solution process red OLED device by doping small molecules 4,4′,4″-tris(N-carbazolyl)-triphenylamine (TcTa) into Poly(9-vinylcarbazole) (PVK) as mixed hole-transporting hosts. The device performance increased from 2 cd/A to 4 cd/A. This is attributed to the energy barrier reduction and better charge balance in the device. The analysis of temperature-dependent hole mobility in PVK:TcTa film indicates that the energetic disorder of PVK:TcTA decreases with increasing concentration of TcTa implying that hole transport is predominately hopping among more ordered TcTa molecules even at low concentration. Second project presents the fabrication of tandem OLED device where a novel solution process charge-generating unit (CGU) using orthogonal solvents is demonstrated. The device efficiency of tandem device shows high current efficiency of 24.2 cd/A at 1000 cd/m2, which is more than three-folds higher than that of single device. This increment is attributed to the efficient CGU developed using PVK blended with 2 wt% of small molecule, 1-Bis[4-[N,N-di(4-tolyl)amino]phenyl]-cyclohexane (TAPC). The investigation on the CGU interface revealed that the energy barrier for hole injection from PVK:TAPC is reduced together with the increasing the hole carrier at the interface. The last project reports a novel solution processes Molybdate (MoO4) as a hole blocking and electron transport interlayer. It is shown that the efficiency of the Super Yellow-phenylenevinylene (SY-PPV) fluorescent-based devices is significantly improved. The improved device showed a current and luminance efficiency up to 22.8 cd/A and 14.3 lm/W respectively, which is more than two-fold higher compared to the control device. Such efficiency enhancement is attributed to the dual functions of MoO4, which serves as a good hole-blocking layer and at the same time able to transport electrons. Ultraviolet Photoelectron Spectroscopy (UPS) measurement shows that the deep lying valence band blocks the excessive holes from leaking into the cathode while low conduction band of MoO4 allowing the electron to be injected from cathode. The observed dual functions of MoO4 make transition metal oxide a very attractive candidate for interfacial modification in various organic electronic devices.